Hydrocortisone dosing in children with classic congenital adrenal hyperplasia: Results of the german/austrian registry - Hoyer-Kuhn, Heike; Huebner, Angela; Richter-Unruh, Anette; Bettendorf, Markus; Rohrer, Tilman; Kapelari, Klaus; Riedl, Stefan; Mohnike, Klaus; Dörr, Helmuth-Günther; Roehl, Friedrich Wilhelm; Fink, Katharina; Holl, Reinhard W.; et al. (Endocrine Connections, 2021)
Objective: Treatment of classic congenital adrenal hyperplasia (CAH) is necessary to compensate for glucocorticoid/mineralocorticoid deficiencies and to suppress androgen excess. Hydrocortisone (HC) is preferred in growing children with classic CAH but recommendations regarding dosage/administration are inconsistent. The aim of this study was to evaluate HC dosing in children with CAH in relation to chronological age, sex, and phenotype based on a multicenter CAH registry. Design: The CAH registry was initiated in 1997 by the AQUAPE in Germany. On December 31st 2018, data from 1571 patients were included. Methods: A custom-made electronic health record software is used at the participating centers. Pseudonymized data are transferred for central analysis. Parameters were selected based on current guidelines. Descriptive analyses and linear regression models were implemented with SAS 9.4. Results: We identified 1288 patients on exclusive treatment with hydrocortisone three times daily (604 boys; median age 7.2 years; 817 salt-wasting phenotype, 471 simple-virilizing phenotype). The mean (lower-upper quartiles) daily HC dose (mg/m² body surface area) was 19.4 (18.9–19.8) for patients <3 months (n = 329), 15.0 (14.6–15.3) for age ≥3–12 months (n = 463), 14.0 (13.7–14.3) for age 1–5.9 years (n = 745), 14.2 (14.0–14.5) for age 6 years to puberty entry (n = 669), and 14.9 (14.6–15.2) during puberty to 18 years (n = 801). Fludrocortisone was administered in 74.1% of patients with a median daily dosage of 88.8 µg. Conclusion: Our analyses showed that still a high proportion of children are treated with HC doses higher than recommended. This evaluation provides comprehensive information on nationwide hydrocortisone substitution dosages in children with CAH underlining the benefit of systematic data within a registry to assess daily practice.
CRIS-Team Scopus Importer:2021-06-11
Keywords: CYP21A2; fludrocortisone; glucocorticoids; treatment